FACILITATING MECHANISM OF THE CREDIT PORTFOLIO QUALITY AND CREDIT RISK MANAGEMENT OF THE BANK IN THE PERIOD OF CRISIS DEVELOPMENTS IN ECONOMIC SPHERE - Dzyublyuk, Oleksandr (Journal of European Economy, 2017)
The improvement trends of the facilitating mechanism of the credit portfolio quality and credit risks management through the definition of the evaluation criterion of the credit quality, creating the credit portfolio of the bank are proved. The creation of the credit portfolio structure in accordance with the group size, classified by the degree of the credit quality, the monitoring of the credit risk, the creation of provisions and adjustment in credit portfolio structure is defined. Special attention is paid to the optimization of the methodology of provisions calculation in order of loan loss provision.